Fatality risk management: Applying Quinlan's Ten Pathways in Western Australia's mining industry. (February 2022) - Jenke, Tanya; Boylan, Jessica L.; Beatty, Shelley; Ralph, Martin; Chaplyn, Andrew; Penney, Greg; Cattani, Marcus
Highlights: Based on Quinlan's 2014 book, which proposes ten pathways to death and disaster. Surveyed > 2000 participants on perception of employer effectiveness in each Pathway. Compared mining industry fatality register with the Quinlan Ten Pathways. Perception of effectiveness in pathways is variable and room for improvement. Results show most of the 71 fatalities reviewed included 4–5 of the 10 pathways. Abstract: In 'Ten Pathways to Death and Disaster' Professor Michael Quinlan (2014) identified a series of ten common catastrophic incident risk factors, known as the Ten Pathways, contributing to major incidents in mining and other high hazard industries. This study applies the Quinlan methodology in two separate phases. The first phase of the study explored employee perception of employer effectiveness of fatality prevention against each of the Ten Pathways through a questionnaire of n = 2009 participants at the 2017–2019 Western Australian Government Mines Safety Roadshows. Respondents generally perceived their employer as having a relatively good understanding of the role of risk assessments and their importance in preventing injuries yet perceived their employers as generally ineffective in management system auditing. In the second phase of the study, 71 fatality reports on the Western Australian Government Department of Mines Fatalities register were assessed to identify the Ten Pathways involved in the fatality. The analysis identified fatalities typically included four or five of the Ten Pathways, although none of the investigations analysed all Ten Pathways. A combined assessment of employee perceptions of employer's effectiveness at fatality prevention and pathways present in the Mines Fatalities register identified which Quinlan Ten Pathways mining organisations should prioritise for fatality prevention. It is recommended that benchmarking safety performance, incident investigations, and reviews of effectiveness of safety management systems include an examination and verification of the organisation's response to Ten Pathways, a relatively straight forward task which may highlight latent issues or weaknesses that may otherwise remain undetected.